Actividades Recreativas para el Desarrollo de la Inteligencia Emocional de los niños de 5 a 6 años - Cajilema Charicando, Norma Isabel (2022)
Education at the kindergarten and high school level allows the development of competencies, abilities and skills in children from 5 to 6 years old, where emotional intelligence is essential to improve children's learning and coexistence. Therefore, it started from the previous project with the theme "Parenting styles in the development of social skills in children from 5 to 6 years old", with the objective of diagnosing the influence of parenting styles in the development of social skills through theoretical references to apply the different research instruments to teachers, parents and students in order to determine the strengths and weaknesses of the “San José de Guaytacama” Educational Unit children, relying on an inductive method. Therefore, the proposal "Recreational activities for the development of the emotional intelligence of children from 5 to 6 years old" was born, with the objective of designing the didactic guide "The madness of emotions" selecting recreational activities for the development of the emotional intelligence of infants in the first years of life, based on the needs detected in the theoretical framework of the previous project. Finally, the proposal consisting of 10 recreational activities on emotional intelligence and social skills was validated by experts and users, who rated the guide as excellent, therefore the guide application will provide significant contributions in strengthening the development of social skills and emotional intelligence such as attachment, empathy, assertiveness, cooperation, communication, self-control and problem solving, allowing recognition and emotional management at an early age.